2016
DOI: 10.1093/infdis/jiw213
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence That HIV-1 Subtype C Infection Compromises the Efficacy of Tenofovir-Containing Regimens: Cohort Study in the United Kingdom

Abstract: Concern has been expressed that tenofovir-containing regimens may have reduced effectiveness in the treatment of human immunodeficiency virus type 1 (HIV-1) subtype C infections because of a propensity for these viruses to develop a key tenofovir-associated resistance mutation. We evaluated whether subtype influenced rates of virological failure in a cohort of 8746 patients from the United Kingdom who received a standard tenofovir-containing first-line regimen and were followed for a median of 3.3 years. In un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Mutations conferring NRTI drug resistance differ little between subtypes, however, and do not seem to affect outcomes. 25 , 26 A cohort study 17 in a subtype-B population drew similar conclusions with respect to predicted NRTI activity and outcomes. For our binary classification of NRTI drugs as active or inactive we used a cutoff (NRTI considered active if no more than low-level resistance) that corresponds to the way many clinicians interpret resistance tests.…”
Section: Discussionmentioning
confidence: 85%
“…Mutations conferring NRTI drug resistance differ little between subtypes, however, and do not seem to affect outcomes. 25 , 26 A cohort study 17 in a subtype-B population drew similar conclusions with respect to predicted NRTI activity and outcomes. For our binary classification of NRTI drugs as active or inactive we used a cutoff (NRTI considered active if no more than low-level resistance) that corresponds to the way many clinicians interpret resistance tests.…”
Section: Discussionmentioning
confidence: 85%
“…Virtually all amino acid differences between subtypes are polymorphisms: variants that occur commonly in the absence of therapy and have little, if any, phenotypic or clinical effect on antiretroviral drugs (ARVs). Thus, most studies suggest that individual ARVs and standard ART regimens are similarly active, regardless of subtype [56–63]. Increased risk of virologic failure has been associated with particular subtypes, but most studies are confounded by geographic location, treatment facilities, and clinical, social, and economic statuses that could affect outcome differences among individuals infected with different subtypes [64–67].…”
Section: Effect Of Subtype On Hiv-1 Drug Resistancementioning
confidence: 99%
“…Second, K65R emerges more rapidly during in vitro passage of subtype C viruses than during passage of subtype B viruses in the presence of tenofovir (Brenner et al, 2006). Third, three retrospective studies have suggested that in patients who develop VF on a TDF-containing regimen are at a somewhat higher risk of developing K65R if they are infected with a subtype C virus (TenoRes Study, 2016; Theys et al, 2013; White et al, 2016). Despite the reported tendency to acquire the K65R DRM, a recent study showed that when demographic and clinical factors are controlled for among patients receiving at TDF-containing regimen, infection with a subtype C virus does not increase the risk of developing VF (White et al, 2016).…”
Section: Effect Of Subtype On Hiv-1 Drug Resistancementioning
confidence: 99%